MEASUREMENT OF KNOWLEDGE LEVEL, UNDERSTANDING OF TAXATION REGULATIONS, AND AWARENESS OF PRIVATE TAXPAYER COMPLIANCE AT PRATAMA KARANGANYAR TAX SERVICE OFFICE - Samhudi Samhudi; Istiatin Istiatin; Ida Aryati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The research that has been carried out has the aim of being able to determine the influence of tax knowledge, understanding of tax regulations, and awareness of paying taxes on a variable called tax payment compliance at KPP Pratama Karanganyar. The research that has been done uses an approach called quantitative. The population in this study consisted of all individual taxpayers at KPP Pratama Karanganyar, all of which were 8708 people. The sample amounted to 100 people. The sampling technique used purposive sampling technique. The technique for data analysis in this research that has used an analysis called multiple linear regression. The results of a study that has been conducted show that tax knowledge, understanding tax regulations, and awareness of paying taxes have a positive and significant impact on a variable called tax payment compliance at KPP Pratama Karanganyar. It is expected that in the future, KPP Pratama Karanganyar will continue to maintain and improve the quality of tax knowledge, understanding of tax regulations, and awareness of paying existing taxes, so that tax payment compliance will also continue to increase and of course be better than before. Keywords: Tax Payment Compliance, Tax Knowledge, Understanding Tax Regulations, Tax Paying Awareness